A Thought Too Far: A Case for a Corpus Approach to Bad Knowledge in Old English Literature - Rían Boyle (SELIM)
This paper explores the results of a pilot study that made use of corpus linguistic and other big data tools to explore the literary and cultural function of knowledge in Old English literature. In particular, it focusses on Bad Knowledge, knowledge that lay outside the confines of social acceptability, and that was used to label people, objects or ideas as evil. Knowledge is a complicated idea in the medieval period, and the discourses around the moral qualitites of knowledge can be traced from antiquity, through to Ælfric of Eynsham, and beyond. However, there exists no easily discernible set of sources that describe epistemological attitudes in vernacular Early English writing. As such, this paper breaks from traditional close reading practices, and turns to a novel, data-based, computational methodology to examine nearly two hundred sentences from ninety-seven different texts, all of which are related to Bad Knowledge. In doing so, it attempts to piece together a framework for what Bad Knowledge may have looked like in the Early English period, and explore the broader relationship of the connections between knowledge, order, and authority. Additionally, it seeks to demonstrate the relevance of computational methods to Old English, and provide a launchpad for future work.